Validation of the modified NUTrition Risk Score (mNUTRIC) in mechanically ventilated, severe burn patients: A prospective multinational cohort study. Issue 8 (December 2021) - Alfonso Ortiz, L.; Jiang, Xuran; Turgeon, Alexis F.; Wibbenmeyer, Lucy; Pollack, Jonathan; Mandell, Samuel P.; Day, Andrew G.; Heyland, Daren K.
Highlights: Not all burn patients are the same, those at highest nutritional risk may benefit the most. The development and validation of nutrition risk assessment tools in burn settings is in its infancy. We have demonstrated the validity of mNUTRIC as a nutritional-risk assessment tool in severe burn patients. In severe burns the mNUTRIC identifies those with a worse prognosis and patients who benefit the most from optimal nutrition. Increased nutrition intake is associated with better clinical outcomes severe burn patients with a high mNUTRIC score. Abstract: Background: Whether nutrition therapy benefits all burn victims equally is unknown. To identify patients who will benefit the most from optimal nutrition, the modified Nutrition Risk in Critically Ill (mNUTRIC) Score has been validated in the Intensive Care Unit. However, the utility of mNUTRIC in severe burn victims is unknown. We hypothesized that a higher mNUTRIC (≥5) will be associated with worse clinical outcomes, but that greater nutritional adequacy will be associated with better clinical outcomes in patients with higher mNUTRIC score. Methods: This prospective study included data from mechanically ventilated, severe burn patients (n = 359) from 51 Burn Units worldwide included in a randomized trial. Our primary and secondary outcomes were hospital mortality and the time to discharge alive (TTDA) from hospital. We described the association between nutrition performance and clinical outcomes. Results: Compared to low mNUTRIC (n = 313), the high mNUTRIC group (n = 46) had higher mortality (61% vs. 19%, p = 0.001), and longer TTDA (>90 [87–>90] vs. 64 [38–90] days, p = <0.0001). Only in the high mNUTRIC group, increased calorie intake (per 20% increase) was associated with lower mortality and a faster TTDA. Conclusions: The mNUTRIC score identifies those with poor clinical outcomes and may identifies those mechanically ventilated, severe burn patients in whom optimal nutrition therapy may be more advantageous.